2010
DOI: 10.15448/1980-6108.2010.1.5927
|View full text |Cite
|
Sign up to set email alerts
|

Congenital toxoplasmosis: Auditory and language outcomes in early diagnosed and treated children

Abstract: Aims: To describe the auditory and language outcomes of children with early diagnosis and treatment for congenital toxoplasmosis. Methods: A cross-sectional study included all children diagnosed with congenital toxoplasmosis, through the Minas Gerais State Neonatal Screening Program, from September 2006 to March 2007. All children received early treatment, initiated before the age of 2.5 months, and were periodically assisted by a team of specialists including pediatricians, ophthalmologists and speech-languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 11 publications
7
28
0
Order By: Relevance
“…The occurrence of retrocochlear auditory disorders in 20.8% of the SG children in the present study is similar to that found in the literature, between 21.1 and 35.5% 4,11,25 . However, it differed from other studies in which the prevalence found was significantly lower or even zero 14,23,26,27 .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The occurrence of retrocochlear auditory disorders in 20.8% of the SG children in the present study is similar to that found in the literature, between 21.1 and 35.5% 4,11,25 . However, it differed from other studies in which the prevalence found was significantly lower or even zero 14,23,26,27 .…”
Section: Discussionsupporting
confidence: 92%
“…The greater occurrence of cochlear loss in the CG of the present study was not expected and may be justified by the reduced number of the sample or by the fact that 50% of the cochlear hearing losses are of genetic origin 22 . The occurrence of cochlear loss in the SG (2.1%) is similar to the result of a study with treated children with congenital toxoplasmosis, which obtained 3.8% of cochlear losses 11 . These results are in contrast to studies conducted in Europe and the United States which, with the same drug therapy used in the present study, observed a reduction of auditory sequelae with early detection and treatment of congenital toxoplasmosis 14,23 .…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations